Analisis Manajemen Kepemimpinan Kepala Sekolah dalam menerapkan MBS di SMP Al-Fudhola' Kecamatan Sungai Lilin Kabupaten Musi Banyuasin - Abdul Rohim; Desy Seplyana; Supriadi Supriadi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to analyze the principal's leadership in implementing School-Based Management (SBM) at Al-Fudhola' Junior High School in Sungai Lilin District, Musi Banyuasin Regency. The research method used was a qualitative descriptive approach, with the principal as the research subject. Data collection techniques included in-depth interviews, participant observation, and documentation. Thematic analysis with data triangulation was used to enhance the validity of the findings. The results indicate that the principal's leadership in implementing SBM has been quite effective through participatory planning, clear organization, teacher empowerment, relatively transparent budget management, and the involvement of parents and the community in decision-making. Despite the challenges of limited infrastructure and budget management, which require appropriate prioritization, the study concludes that participatory, transparent, and accountable principal leadership plays a crucial role in the successful implementation of SBM and needs to be supported by strengthening infrastructure and increasing the involvement of all stakeholders to continuously improve educational quality. Keywords: Principal Leadership, School-Based Management, Educational Quality, Participation, Junior High School